Life stage, not climate change, explains observed tree range shifts - Máliš, František; Kopecký, Martin; Petřík, Petr; Vladovič, Jozef; Merganič, Ján; Vida, Tomáš (Global change biology, 2016)
Ongoing climate change is expected to shift tree species distribution and therefore affect forest biodiversity and ecosystem services. To assess and project tree distributional shifts, researchers may compare the distribution of juvenile and adult trees under the assumption that differences between tree life stages reflect distributional shifts triggered by climate change. However, the distribution of tree life stages could differ within the lifespan of trees, therefore, we hypothesize that currently observed distributional differences could represent shifts over ontogeny as opposed to climatically driven changes. Here, we test this hypothesis with data from 1435 plots resurveyed after more than three decades across the Western Carpathians. We compared seedling, sapling and adult distribution of 12 tree species along elevation, temperature and precipitation gradients. We analyzed (i) temporal shifts between the surveys and (ii) distributional differences between tree life stages within both surveys. Despite climate warming, tree species distribution of any life stage did not shift directionally upward along elevation between the surveys. Temporal elevational shifts were species specific and an order of magnitude lower than differences among tree life stages within the surveys. Our results show that the observed range shifts among tree life stages are more consistent with ontogenetic differences in the species' environmental requirements than with responses to recent climate change. The distribution of seedlings substantially differed from saplings and adults, while the distribution of saplings did not differ from adults, indicating a critical transition between seedling and sapling tree life stages. Future research has to take ontogenetic differences among life stages into account as we found that distributional differences recently observed worldwide may not reflect climate change but rather the different environmental requirements of tree life stages.
Keywords: distribuce rostlin; tree life stages; vegetation resurvey; Trees; elevational range shift; druhová specificita; Forests; Plant Dispersal; lesy; stromy; Slovakia; Slovenská republika; časové faktory; temperate forests; klimatické změny; semipermanent plots; Climate Change; Altitude; realized niche; Species Specificity; tree ontogeny; Time Factors; nadmořská výška